Closing the achievement gap a vision for changing beliefs and practices - Supervision and Curriculum Development (Alexandria, VA : ASCD, 2004)
Summarizes the ideas and strategies for integrating theory and research with current reform proposals to address achievement differences presented in AFCD's book. Highlights work done by teachers at Toquam School in Stamford, Connecticut, where teachers use knowledge of normal human development in varied contexts to apply a comprehensive approach to learning that involves integrating neuroscience, cognition and sociocultural policy
Title from title screen
This program is based on the ASCD book'closing the achievement gap: a vision for changing beliefs and practices, 2nd edition'
Keywords: Children with social disabilities -- Education -- United States; Education, Urban -- Social aspects -- United States; Academic achievement -- United States; Educational change -- United States